Go legal yourself : know your business legal lifecycle - Bagla, Kelly (John Wiley & Sons, Inc., 2021)
"There is one thing that every business owner has in common --the pains and heartaches of running a business. If luck most avoid major pitfalls and eventually become successful. Most entrepreneurs are too busy starting their busy to pay attention to the numerous legal details that are involved in the life cycle of a business (nor is there much disposable income to spend on lawyers). This is a guide for business owners that explains the four phases of the legal lifecycle of their business and how to set up your business for success from day one"--